THE INFLUENCE OF COMPETENCY FACTORS, CAREER DEVELOPMENT AND MOTIVATION ON THE PERFORMANCE OF NCO PERSONNEL PROSPECTIVE FOR THE INDONESIAN NAVY'S DIKTUKPA STUDENTS - Eko Kurniawan; Suparno Suparno; Adi Bandono; Joko Purnomo (JOURNAL ASRO, 2021)
Improved personnel performance will bring progress for the institution to be able to carry out its duties. Therefore, efforts to improve personnel performance are the most serious challenges for leaders because the success in achieving goals depends on the quality of the performance of human resources in it. The purpose of this study was to analyze the variables that have an effect on improving the performance of the Indonesian Navy's Diktukpa students Candidates including competence, career development and soldier motivation. The method used is a quantitative method with Structural Equation Model (SEM) analysis and AMOS software. The results showed that the competency variable had an adequate influence on performance although it was not significant. The soldier career development variable has a significant effect on the performance variable of the NCO soldier candidates for the Indonesian Navy's Diktukpa students. The soldier competency variable has a very significant influence on the motivation of the NCO soldier candidates for the Indonesian Navy's Diktukpa students. The soldier career development variable has a significant influence on the motivation of the NCO soldier candidates for the Indonesian Navy's Diktukpa students. The soldier's motivation variable has a sufficient influence on the performance of the NCO soldier candidates the Indonesian Navy's Diktukpa students even though it is categorized as less significant. The analysis of the results can be used as a basis for input in the formulation of strategies and policies as well as efforts to improve the performance of Naval Air Force candidates for the Indonesian Navy's Diktukpa students, given the very important function of the presence of NCO members who are the liaison between officers and enlisted. By increasing the performance of Naval Forces candidates for the Indonesian Navy's Diktukpa students, it will automatically improve the performance of the Indonesian Navy organization. Keywords: Competence, Career Development, Motivation, Employee Performance, Structural Equation Modelling (SEM).